Kajian Viktimologis Terhadap Korban Jiwa Akibat Kecelakaan Lalu Lintas Di Wilayah Hukum Kepolisian Daerah Nusa Tenggara Timur - Ivan, Ivan Yafferson Kadja; Adrianus Djara Dima; Sigit Prabowo Sonbait (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the high number of traffic accidents resulting in fatalities within the jurisdiction of the Regional Police of East Nusa Tenggara, as well as the importance of legal protection for victims from a victimological perspective. Based on this background, the research problems are formulated as follows: (1) How is the legal protection for fatal victims of traffic accidents within the jurisdiction of the Regional Police of East Nusa Tenggara? (2) What are the obstacles in providing legal protection for such victims in the region? The purpose of this study is to identify and analyze the forms of legal protection and the obstacles encountered in efforts to protect victims of fatal traffic accidents. The research method used is an empirical juridical approach with a qualitative method. Data were obtained through interviews and document studies conducted at the Traffic Directorate of the Regional Police of East Nusa Tenggara and PT Jasa Raharja. The data were analyzed descriptively and qualitatively to comprehensively describe the legal protection for fatal victims and the obstacles encountered in practice. The results of the study indicate that legal protection for victims of fatal traffic accidents is carried out through three forms, namely compensation (damages), restitution, and state compensation. Damages are provided by the offender to the victim’s family, restitution is granted through court decisions as a form of the offender’s responsibility, while compensation is provided by the state through PT Jasa Raharja as a form of social security. However, in practice, there are still several obstacles, such as lack of public awareness, administrative constraints, the limited economic capacity of offenders, and suboptimal coordination among institutions. This study is expected to contribute to the development of criminal law and victimology, as well as serve as a reference for law enforcement agencies and the government in improving legal protection for victims of traffic accidents in the future.